Dreams and Visions: Critical Realism, Practical Theology, and the Spiritual Experiences of Pioneers Discerning the Missio Dei - Bradbury, Paul (Ecclesial Futures, 2020)
This article develops a narrative framework toward a methodology for my research exploring the call and practice of pioneer ministers in the Church of England. I argue for a critical realist perspective as a means of affirming and valuing spiritual experience as a locus for knowledge. Drawing on the work of Alasdair MacIntyre and NT Wright a narrative framework of “intelligibility” is developed in which to place such testimonies of experience. This framework is then shaped by a biblical pneumatology whereby the work of salvation is driven forward toward the telos of the Kingdom by the mediation of the Holy Spirit. The value of this framework is explored in light of my future research into the experiences of pioneer ministers for whom discerning the missio Dei is a key part of their call and ongoing ministry in innovative mission and ecclesial reimagination. Attention is therefore given to the implications of this for practical theology and for spiritual discernment as a part of a methodology of empirical research.